Comparative analysis of ovarian transcriptomes between prolific and non‐prolific goat breeds via high‐throughput sequencing. (14th November 2017) - Zi, X‐D; Lu, J‐Y; Zhou, H; Ma, L; Xia, W; Xiong, X‐R; Lan, D‐L; Wu, X‐H
Contents: To increase the current understanding of the gene expression in the pre‐ovulatory ovary and identify the key genes involved in the regulation of ovulation rate, we compared the transcriptomes of ovaries from the prolific Jintang black goat (JTG) and the non‐prolific Tibetan goat (TBG) during the follicular phase using the Illumina RNA‐Seq method. Three ovarian libraries were constructed for each breed. On average, we obtained approximately 49.2 and 45.9 million reads for each individual ovary of TBGs and JTGs, respectively, of which 79.76% and 78.67% reads were covered in the genome database. A total of 407 differentially expressed genes (DEG) were detected between these two breeds, in which 316 were upregulated, and 91 were downregulated in the ovaries of JTGs versus TBGs. Based on the results of Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment, some of these DEGs potentially play an important role in controlling the development of ovarian follicles. SRD5A2, MSMB, STAR and 3BHSD, etc. were the most significantly differentially expressed between these two distinct breeds. In addition, each ovary expressed 1, 066 versus 989 novel transcripts, and 171, 829 versus 140, 529 putative SNPs in TBGs versus JTBs, respectively. All data sets (GEO and dbSNP) were available via public repositories. Our study provides insight into the transcriptional regulation of the ovaries of two distinct breeds of goats that might serve as a key resource for understanding goat fecundity. SRD5A2, MSMB, STAR and 3BHSD may be associated with the high fecundity of JTGs.